TO BEETLE OR NOT TO BEETLE: ASSESSING ENGELMANN SPRUCE FOREST RESILIENCE FOLLOWING SPRUCE BEETLE OUTBREAK IN WESTERN COLORADO - Snyder, Vausha Elise, author; Stevens-Rumann, Camille, advisor; Battaglia, Mike A., committee member; Rocca, Monique, committee member (Colorado State University. Libraries, 2026)
Bark beetle outbreaks are affecting millions of hectares globally. In the southern Rocky Mountains, native spruce bark beetles (Dendroctonus rufipennis) are a natural disturbance agent in subalpine forests, but recent outbreaks have increased in severity, resulting in landscape-scale changes in forest composition and structure. These beetles primarily affect Engelmann spruce (Picea engelmannii) trees larger than 40 cm in diameter. Following outbreak, post-disturbance recovery may be influenced by previous management, stand composition, and regeneration dynamics. In this study we examined three questions: (1) How do different species (e.g., Engelmann spruce, aspen) respond to treatments under varying climate conditions? (2) Under different climate scenarios, will spruce recruitment be sufficient to maintain forest structure and composition, or will other species (e.g., aspen) become dominant? (3) How do treatments affect forest structure, and how do these treatments promote long-term resilience to future disturbances (e.g., fire, drought, secondary insect outbreaks)? To evaluate these questions, 44 repeatedly measured plots, and 66 additional inventory plots in south-central Colorado in previously managed, unmanaged, and salvaged, and no-beetle reference stand were analyzed. Future stand trajectories were then projected using the Forest Vegetation Simulator (FVS). Regeneration responses differed among species, with aspen increasing in larger seedling height classes while spruce recruitment declined in the smallest size class (0.1- 9.9 cm; Class 1). Seedling responses to vapor pressure deficit differed by species despite no significant overall effect on seedling density. Modeled tree density differed significantly among species and disturbance history, indicating species life-history traits and beetle disturbance history were stronger drivers of projected stand structure than management history alone. Regeneration-based species composition also differed significantly among pre-disturbance, current, and future regeneration based communities, indicating continued composition shifts following disturbance. These results suggest that post-disturbance regeneration dynamics may influence future forest composition depending on pre-disturbance species composition and species-specific life-history traits. Engelmann spruce is projected to persist on the landscape, albeit at lower densities and often with greater aspen presence. These findings indicate that disturbance history, regeneration dynamics, and management decisions interact to influence long-term forest composition, emphasizing the need to integrate adaptation strategies with long-term monitoring to support resilience in high-elevation subalpine ecosystems.
Keywords: Engelmann Spruce; Forest Resilience; Subalpine Forests; Forest Composition; Aspen (Populus tremuloides); Spruce Beetle